PENGUJIAN PENGARUH PENAMBAHAN ATTAPULGITE SEBAGAI VISCOSIFIER TERHADAP SIFAT FISIK LUMPUR PEMBORAN - Ariyanto, Adam; Risna, Risna; Mukmin, M Nur (Sekolah Tinggi Teknologi MIGAS, 2025)
The success of a drilling operation depends on the conditions and mud system used. Changes in the physical properties of the mud are caused by contamination from NaCl, which occurs when drilling penetrates a high-salt dome and enters the drilling mud.The purpose of this research is to investigate the effect of adding Bentonite and Attapulgite additives on the properties of drilling mud. This research uses an experimental method.The results show that the density of the mud remains constant in the range of 1.04-1.06 ppg, even when Attapulgite is added up to 4 grams, because the use of barite remains at 25 grams. The addition of Attapulgite increases the plastic viscosity from 13 cp in sample 1 to 24 cp in sample 5, increases the yield point from 30 lb/100ft² to 62 lb/100ft², making the mud more effective in transporting drill cuttings. The gel strength increases from 11 lb/100ft² to 15 lb/100ft², meeting API standards. The filtrate decreases from 8.4 mL in sample 3 to 6.6 mL in sample 5, indicating Attapulgite's ability to control filtration. The mud cake thickness remains thin (0.13-0.18 mm), in accordance with API standards. Conclusion The addition of Attapulgite in the amount of 1-4 grams shows an increase in various parameters. Attapulgite is effective as an additive for controlling filtration loss, with test results showing a decrease in filtrate volume in all samples.